Ammonia-oxidizing archaea and complete ammonia-oxidizing Nitrospira in water treatment systems. (1st May 2022) - Al-Ajeel, Sarah; Spasov, Emilie; Sauder, Laura A.; McKnight, Michelle M.; Neufeld, Josh D.
Highlights: AOA and comammox  Nitrospira  dominate low ammonia engineered environments. Ammonia and metal levels, along with temperature determine the niches of nitrifiers. Contributions to nitrification cannot be inferred solely by AOA or AOB abundances. Comammox Nitrospira may play an important role in engineered systems nitrification. Methods like SIP and FISH may help discern contributions from nitrifying guilds. Abstract: Nitrification, the oxidation of ammonia to nitrate via nitrite, is important for many engineered water treatment systems. The sequential steps of this respiratory process are carried out by distinct microbial guilds, including ammonia-oxidizing bacteria (AOB) and archaea (AOA), nitrite-oxidizing bacteria (NOB), and newly discovered members of the genus Nitrospira that conduct complete ammonia oxidation (comammox). Even though all of these nitrifiers have been identified within water treatment systems, their relative contributions to nitrogen cycling are poorly understood. Although AOA contribute to nitrification in many wastewater treatment plants, they are generally outnumbered by AOB. In contrast, AOA and comammox Nitrospira typically dominate relatively low ammonia environments such as drinking water treatment, tertiary wastewater treatment systems, and aquaculture/aquarium filtration. Studies that focus on the abundance of ammonia oxidizers may misconstrue the actual role that distinct nitrifying guilds play in a system. Understanding which ammonia oxidizers are active is useful for further optimization of engineered systems that rely on nitrifiers for ammonia removal. This review highlights known distributions of AOA and comammox Nitrospira in engineered water treatment systems and suggests future research directions that will help assess their contributions to nitrification and identify factors that influence their distributions and activity. Graphical abstract: Image, graphical abstract